Fostering Municipal Support for Legacy Businesses through Worker Cooperative Conversions: Strategies for Boston - Li, Emily (Tufts University Tisch Library, 2025)
Thesis (M.A.)--Tufts University, 2025.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Penn Loh.; Committee: Jeffrey Rosen.; Keywords: Public policy, and Urban planning